The effects of time-restricted feeding on early phases of carcinogenesis in rat liver and colon - Malakmahmoudi, Nadia; Pisu, Roberta; Barbarossa, Andrea; Pisu, Francesca; Porcu, Giuseppe S.; Laconi, Ezio; Perra, Andrea; Uzzau, Sergio; Marongiu, Fabio (Frontiers in Nutrition, 2026)
Background and aimsHigh-fat diets are established contributors to carcinogenesis through mechanisms involving altered lipid metabolism, metabolic stress, and chronic inflammation. Time-restricted feeding (TRF) has emerged as a promising non-pharmacological strategy to improve metabolic health and potentially mitigate cancer risk by optimizing glycemic control, lipid profile, and inflammatory triggers. Despite these potential benefits, the direct impact of TRF on early-stage carcinogenesis, particularly in the context of obesogenic dietary conditions, remains inadequately explored. This study aimed to investigate the effects of TRF on the development of preneoplastic lesions in the liver and colon in male and female rats exposed to high-fat (HFD) and low-fat (LFD) diets.MethodsCarcinogenesis was initiated using diethyl nitrosamine (DENA) for the liver and azoxymethane (AOM) for the colon. Rats were assigned to ad libitum feeding (AdL) or TRF (8-h feeding window) following carcinogen exposure and were euthanized at 6 or 9 months for assessment. Pre-neoplastic lesions in the liver were evaluated by glutathione S-transferase placental form (GSTP)-positive staining, while aberrant crypt foci (ACF) were analyzed in the colon. Additionally, hepatic steatosis and metabolic parameters were assessed to determine the impact of TRF.ResultsNo differences were observed in the incidence, size, or distribution of GSTP-positive lesions in the liver or ACF in the colon between TRF and AdL groups. TRF also failed to reduce hepatic steatosis or improve serum lipid profiles in animals fed an HFD.ConclusionOur findings indicate that TRF does not significantly alter the development of early preneoplastic lesions in the liver or colon, regardless of dietary fat content, and further suggest that this dietary regimen is insufficient alone to counteract metabolic dysfunctions induced by highly obesogenic diets in rats.